2016
DOI: 10.1371/journal.pone.0155514
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Salubrinal on the Cartilage and Subchondral Bone of the Temporomandibular Joint under Various Compressive Mechanical Stimulations

Abstract: Excessive mechanical loads on the temporomandibular joint (TMJ) can cause mandibular cartilage degradation and subchondral bone erosion, but the treatment of these conditions remains challenging. Salubrinal, which target eukaryotic translation initiation factor 2 alpha, has been shown to have multiple beneficial effects on skeletal tissue. Here, we examined the effect of a Salubrinal injection on the mandibular cartilage and subchondral bone of the TMJ under various compressive stresses. We conducted in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Although counter-intuitive, a similar effect was previously observed in multiple myeloma 53 and leukemic cells 54 and suggests further salubrinal-mediated effects, which are yet not completely understood in detail. However, as salubrinal exerts protective effects in noncancerous tissues 55,56 , it might be a promising sensitizer for anticancer approaches targeting proteotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although counter-intuitive, a similar effect was previously observed in multiple myeloma 53 and leukemic cells 54 and suggests further salubrinal-mediated effects, which are yet not completely understood in detail. However, as salubrinal exerts protective effects in noncancerous tissues 55,56 , it might be a promising sensitizer for anticancer approaches targeting proteotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The ACL insertions and articular cartilages of the medial tibial condyle from each animal were fixed in neutral-buffered formalin, decalcified and embedded in paraffin 10 , 16 , 17 ) . The specimens were stained with hematoxylin and eosin and safranin O 10 , 16 , 17 ) . Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick-end labeling (TUNEL) was performed to detect apoptotic cells ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“… ), and proliferating cell nuclear antigen (PCNA) was used to detect proliferating cells ( Fig. 1b ) using previously described methods 10 , 16 , 17 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that excessive mechanical stress is an important etiological factor of TMJ OA [1][2][3][4]. We have successfully constructed the TMJ OA rat model induced by compressive mechanical stress [5][6][7][8][9][10]. Previous studies reported that the thinning of the cartilage, subchondral bone resorption, and extracellular matrix (ECM) damage are the main pathological changes induced by excessive mechanical stress [7][8][9].…”
Section: Introductionmentioning
confidence: 99%